Stillbirth prevalence in Brazil: an exploration of regional differences - Taiana Silva Carvalho; Lucia Campos Pellanda; Pat Doyle
Abstract Objective Brazil is a large, heterogeneous, and diverse country, marked by social, economic, and regional inequalities. Stillbirth is a global concern, especially in low- and middle-income countries. This study investigated the prevalence and possible determinants of stillbirth in different regions of Brazil. Methods This is a cross-sectional study including all women of reproductive age who had had a pregnancy in the last five years, enrolled in the most recent Brazilian Demographic and Health Survey (DHS/PNDS-2006/07). Logistic regression was used to assess the association between region and other maternal characteristics and stillbirth risk. Results The prevalence of stillbirth in Brazil was 14.82 per 1000 births, with great variation by region of the country, and a higher prevalence among the most deprived. The North and Northeast regions had the highest odds of stillbirth compared to the Center-West, which persisted after adjustment for multiple confounders - including deprivation level and ethnicity. Low maternal age and maternal obesity were also related to higher odds of stillbirth. Conclusion In Brazil, the region influences stillbirth risk, with much higher risk in the North and Northeast. Variation in socioeconomic level does not explain this finding. Further research on the subject should explore other possible explanations, such as antenatal care and type of delivery, as well as the role of the private and public health systems in determining stillbirth. Preventive strategies should be directed to these historically disadvantaged regions, such as guaranteeing access and quality of care during pregnancy and around the time of birth.